Abductor recovery after muscle-sparing periacetabular osteotomy using a lateral approach. Issue 4 (13th December 2022) - Nakashima, Yasuharu; Hara, Daisuke; Ohishi, Masanobu; Motomura, Goro; Kawano, Ichiro; Hamai, Satoshi; Kawahara, Shinya; Sato, Taishi; Yamaguchi, Ryosuke; Utsunomiya, Takeshi; Kitamura, Kenji
ABSTRACT: To decrease hip abductor dysfunction after periacetabular osteotomy using a lateral/trochanteric approach, we aimed to modify transposition osteotomy of the acetabulum (TOA) to not cut the greater trochanter and abductor–iliac crest detachment. We subsequently compared abductor muscle strength recovery between TOAs with [conventional TOA (C-TOA)] and without [modified TOA (M-TOA)] trochanteric osteotomy. C-TOA and M-TOA were performed in 27 and 34 hips, respectively. Hip abduction, flexion and knee extension muscle strength were measured preoperatively and at 3, 5, 10, 24 and 52 weeks postoperatively. The muscle strength ratio of the affected and contralateral lower limbs was compared between the C-TOA and M-TOA groups. Neither the mean Merle d'Aubigné–Postel score at the final follow-up nor the postoperative center-edge angle showed significant differences between the M-TOA and C-TOA groups (15.7 versus 16.4 points; P  = 0.25 and 38.5° versus P  = 0.62 and 39.8°, respectively). The mean muscle strength ratios of hip abduction at 5, 12 and 24 weeks postoperatively were significantly higher in the M-TOA group than in the C-TOA group (0.62 versus 0.39, 0.76 versus 0.59 and 0.94 versus 0.70; P  = 0.03, 0.04 and 0.01, respectively). There were no significant differences between groups at Postoperative Week 52 ( P  = 0.36). Discomfort at the greater trochanter was observed in 18 hips (66.7%) in the C-TOA group but only in 4 hips (11.2%) in the M-TOA group. In conclusion, M-TOA is less invasive than C-TOA and allows an earlier recovery of abductor muscle strength without significant correction loss.